2016
DOI: 10.3233/bme-161568
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable/biocompatible coated metal implants for orthopedic applications

Abstract: Biocompatible metals have been suggested as revolutionary biomaterials for bone-grafting therapies. Although metals and their alloys are widely and successfully used in producing biomedical implants due to their good mechanical properties and corrosion resistance, they have a lack in bioactivity. Therefore coating of the metal surface with calcium phosphates (CaP) is a benign way to achieve well bioactivity and get controlled corrosion properties. The biocompatibility and bioactivity calcium phosphates (CaP) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 100 publications
(92 reference statements)
0
20
0
2
Order By: Relevance
“…With exposure to high chloride concentrations such as in a physiological environment, Mg(OH) 2 reacts with chloride ions to produce MgCl 2 , which is highly soluble53. This promotes the rapid dissolution of the Mg coating, with the subsequent production of hydrogen gas and hydroxide ions.…”
Section: Discussionmentioning
confidence: 99%
“…With exposure to high chloride concentrations such as in a physiological environment, Mg(OH) 2 reacts with chloride ions to produce MgCl 2 , which is highly soluble53. This promotes the rapid dissolution of the Mg coating, with the subsequent production of hydrogen gas and hydroxide ions.…”
Section: Discussionmentioning
confidence: 99%
“…98,99 These metal phosphate nanomaterials also present excellent biocompatibility and biodegradability. For example, CaPs are widely used in the field of bone regeneration due to their superior biocompatibility 100 and their unique role in human bone. Compared with other types nanomaterial, metal phosphate nanomaterials are mainly generated via the hydrothermal method, 101 which is relatively simple.…”
Section: Metal Phosphide Nanomaterialsmentioning
confidence: 99%
“…Thus, fractured bone fixtures stimulate BMs to become a huge potential market in orthopedic applications [ 142 ]. Many Mg-based alloys such as ZEK 100, LAE442 and MgCa0.8 have been fabricated into screws for animal models and clinical trials [ 13 , 85 , 143 , 144 ]. A twelve months in vivo animal model confirmed that the Mg-based alloys showed positive osteogenetic effects after implantation.…”
Section: Orthopedic Applicationsmentioning
confidence: 99%